Development of High-voltage Testing System Based on Power Frequency Converter Used in Partial Discharge Tests of Potential Transformers - Tongpian Prombud; Peerawut Yutthagowith (My University, 2020)
We present the development of a high-voltage (HV) testing system based on a power frequency converter in HV and partial discharge (PD) tests of a potential transformer (PT).The converter with the proper filter is utilized as a low-voltage source connected with a HV transformer in the HV and PD tests.The converter is composed of a three-phase rectifier and a power converter based on pulse width modulation (PWM) with a unipolar switching technique.The vital problem in the HV and PD tests is that a converter with a high rate of rise and fall of voltage switching always generates a high noise level that affects the background noise in the PD test.In some PD tests, the noise level is higher than the acceptable level of the PD test requirement in HV equipment such as PTs and distribution transformers.It will be advantageous if an efficient PD testing system based on a power frequency converter can be developed for such tests.In this paper, the proper filter was analyzed and developed to meet the following requirements: the applied HV difference (root mean square voltage and peak voltage/ 2) to the test object and its total harmonic distortion should be less than 5%, and the background noise level in the PD tests should be less than half the acceptable PD level of such HV equipment specified by the relevant standards.In the case of the oil-type PT, the acceptable PD level is only 5 pC, so it is difficult to find a low-cost commercial frequency converter that satisfies this requirement.To verify the developed system, the performance characteristics of the developed converter have been investigated in terms of the background noise in the PD test, the total harmonic distortion of output voltage from the HV testing transformer side, and the input power consumption.The characteristics of the proposed and developed system are analyzed, and experimental results agree well with the simulation ones.The developed system can generate an output voltage of high quality that satisfies the standard requirement.At the test voltage of 40 kV rms , the total harmonic distortion voltage (THD v ) is less than 2% and the background noise is less than 2.5 pC.Moreover, the proper switching frequency and amplitude modulation index (m a ) are investigated, and it is found that the switching frequency from 1 to 20 kHz and m a of 0.8 and 1 do not affect the background noise level or the THD v , and the switching frequency from 1 to 4 kHz and m a of 1 are the best conditions since the input power
Keywords: High Voltage; High voltage insulation and dielectric phenomena